Strategies for optimising the utilization of crop residues and agro-industrial byproducts for livestock feeding in the tropics - Preston, Thomas R. (International Livestock Centre for Africa, 1986)
Presents and discusses alternative approaches to the development of feeding systems. Discusses animal response to non-conventional feed resources, nutritive value, prinicipals of supplementation, and alternative sources of supplements. Relates nutrient supply to productive state.